Development of Radiographer Performance Assessment Instruments in the Radiology Installation of Dr. H. Abdul Moeloek Lampung Province - Soraya, Sri; Sudiyono, Sudiyono; Indrati, Rini (Journal of Social Research, 2023)
At Abdul Moeloek Regional General Hospital in Lampung Province, evaluating radiographers' performance is crucial for ensuring quality radiology services. The current assessment tools for ongoing professional practice and work behavior lack clear, objective indicators and targets. This research uses research and development (R&D) research methods with a quasi-experimental posttest-only non-equivalent control group design. Data were collected using observation, interviews, and FGD. Expert validation and design improvements are conducted, followed by a trial involving 20 radiographers. Validity is tested using corrected items to total correlation, and reliability is assessed using Cronbach's alpha. Next, expert validation tests and design improvements were carried out by 3 experts, and then a limited trial of 20 RSUDAM radiographers carried out a validity test using corrected items to total correlation. Meanwhile, the reliability test uses Cronbach's alpha. The developed instrument, based on indicators and targets, demonstrates valid and reliable measures of radiographer performance. Expert validation through FGD confirms the instrument's effectiveness. Validity test results indicate significance (> 0.05), and reliability tests show Cronbach's alpha values (> 0.60). Normality tests reveal non-distributed data (p-value < 0.05). The Wilcoxon test, comparing old and new instruments, yields a significant Asymp.sig value (0.000) for the discipline variable, indicating improved performance assessment.